Banks and Their Role in Achieving Sustainable Development: An Applied Study on Rafidain Bank - فتاح, ابتسام احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Sustainable development is one of the most pressing contemporary challenges facing societies, as it requires a balance between economic growth, environmental preservation, and social justice. In this context, financial institutions, particularly banks, play a pivotal role in achieving the goals of sustainable development through their financing policies, investments, and support for projects with economic, social, and environmental impact. With the evolution of economic concepts, it has become necessary to reconsider the roles of banks as active tools in comprehensive development, rather than merely traditional lending entities. This research aims to analyze the role of banks, specifically Rafidain Bank, in supporting and implementing the requirements of sustainable development by examining its financing policies, the projects it funds, and its contributions to environmental, social, and corporate social responsibility domains. The importance of the study lies in highlighting the relationship between banking policies and sustainable development goals (SDGs) in Iraq, while uncovering the challenges and opportunities available for banks to effectively contribute to this developmental path. The research problem stems from the relative weakness in the contribution of some Iraqi banks to achieving sustainable development, despite the importance of this role in light of current economic and environmental conditions. From this arises the main research question: To what extent does Rafidain Bank contribute to achieving sustainable development in Iraq? The study hypothesizes the existence of a statistically significant relationship between Rafidain Bank’s developmental activities and the realization of sustainable development dimensions. The study will be conducted on a sample of (30) administrative and executive employees within Rafidain Bank in Baghdad, who are directly involved in policy formulation or in the implementation of financing programs. The research adopts the descriptive-analytical method, using a questionnaire to measure employees’ perceptions regarding the bank’s adoption of sustainable development concepts and practices, in addition to analyzing the bank’s official data and reports. The study seeks to provide practical recommendations that enhance Rafidain Bank’s developmental role and encourage other Iraqi banks to adopt responsible financial policies that support sustainable development goals.